FORMULASI SEDIAAN KRIM EKSTRAK ETANOL DAUN KALIANDRA (Calliandra surinamensis) DAN UJI AKTIVITAS ANTIBAKTERINYA TERHADAP BAKTERI Staphylococcus aureus (PHARMACON, 2019)
ABSTRACTÂ This study aims to test the antibacterial effectiveness of ethanolic extract of Kaliandra leaf cream and evaluate the preparations using parameters of physical properties, physical stability, and sterility. Kaliandra leaf (Calliandra surinamensis) contains compounds such as flavonoid, saponins and tannins that can inhibit the growth of bacteria. This research uses laboratory experimental methods. Cream preparation formula is made with variations in the concentration of ethanol extract of Kaliandra leaves 2%, 3%, 4%, 5%, 6%. Kaliandra leaf extract was obtained by maceration using 96% ethanol solvent. The study of antibacterial test of ethanol extract of Kaliandra leaf extract using the method of Staphylococcus aures produced inhibitory power of 5.09 Â± 0.88 mm at a concentration of 6%. The physical evaluation of the cream preparation includes organoleptic examination (odor, color, shape), homogeneity, pH testing, adhesion, dispersion, cycling test. All tests are carried out before and after the cycling test. The results obtained before and after the cycling test showed that the cream preparations met organoleptic requirements, homogeneity, cream pH 6.07 (4.5-6.5), cream adhesion 4.59 seconds (